Laplace Transform of Cosine/Proof 2

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $\cos$ be the real cosine function.

Let $\laptrans f$ denote the Laplace transform of the real function $f$.


Then:

$\laptrans {\cos a t} = \dfrac s {s^2 + a^2}$

where $a \in \R_{>0}$ is constant, and $\map \Re s > a$.


Proof

\(\displaystyle \laptrans {e^{i a t} }\) \(=\) \(\displaystyle \frac 1 {s - i a}\) Laplace Transform of Exponential
\(\displaystyle \) \(=\) \(\displaystyle \frac {s + i a} {s^2 + a^2}\) multiply top and bottom by $s + i a$

Also:

\(\displaystyle \laptrans {e^{i a t} }\) \(=\) \(\displaystyle \laptrans {\cos a t + i \sin a t}\) Euler's Formula
\(\displaystyle \) \(=\) \(\displaystyle \laptrans {\cos a t} + i \laptrans {\sin a t}\) Linear Combination of Laplace Transforms

So:

\(\displaystyle \laptrans {\cos a t}\) \(=\) \(\displaystyle \map \Re {\laptrans {e^{i a t} } }\)
\(\displaystyle \) \(=\) \(\displaystyle \map \Re {\frac {s + i a} {s^2 + a^2} }\)
\(\displaystyle \) \(=\) \(\displaystyle \frac s {s^2 + a^2}\)

$\blacksquare$


Sources